A dual lane piezoelectric ring bender actuated nozzle-flapper servo valve for aero engine fuel metering. (9th October 2019) - Bertin, Michael; Plummer, Andrew; Bowen, Chris; Johnston, Nigel; Griffiths, Mike; Bickley, Dan
Abstract: Amongst many other high performance flow control applications, servo valves are used to control aero engines by metering the fuel delivered from the fuel pump. Conventionally, a fuel metering servo valve has a pilot stage with an electromagnetic torque motor moving a flapper which differentially restricts a pair of nozzles to create a hydraulic signal (i.e. a pressure difference). These valve pilot stages use mature, optimised technology such that to achieve improvements requires a novel approach. Torque motors in particular present reliability and manufacturing difficulties, and news solutions should ultimately allow a reduction in manual assembly and set-up, improve repeatability, and eliminate failures associated with fine wire devices. In this paper, a pilot stage actuated by piezoelectric ring benders is proposed, designed, built and tested, and test results are compared with a model used to predict pressure-flow characteristics. A particular challenge is the need to include redundancy, and thus a pair of ring benders is used, allowing isolation between duplicated electrical control channels. Another challenge is the mounting of the ring bender, which has to flex to allow the outer edge of the ring bender to deform, yet be stiff enough to adequately react against generated forces. O-ring mounts made from three different elastomer materials are compared in this study. In aerospace, an added complication is the large range of fuel temperature; F70 fluorosilicone O-rings have been chosen with this in mind, and successfully demonstrated in the range −50 °C to +180 °C. With one active and one inactive ring bender to simulate a failure condition, the new dual lane pilot stage achieves +/−50 μ m displacement under test, giving control port flows up to +/−0.6 l min −1, and a control port pressure variation of 40 bar using a 100 bar supply pressure difference (supply minus return pressure). This research establishes that a piezoelectric aero engine fuel valve is feasible, and in particular, that piezoelectric ring bender actuators with elastomeric mountings are highly suited to this application.